Features of transformation of labor potential into human capital in the conditions of deepening demographic crisis (Regional aspects of productive forces development of Ukraine, 2020)
The employment potential has been steadily declining in Ukraine for the recent decades. The number of economically active population, which is the basis of labor potential has been declining, so there are concerns about the prospects of providing the national economy with living labor resources. Today, the human factor has become a priority in the system of "man-economy" and therefore the problem of labor potential formation and its transformation into human capital has become especially relevant. Considering the labor potential as an opportunity for the economically active population to provide the national economy with living labor resources, the nature of demographic and migration processes in the country and in particular in most regions is a matter of concern. As a result of these processes, there is an undesirable for the society, deterioration of the quality structure of labor potential: the working age population is reduced, there is an increase in emigration, especially of young people, for favorable employment and training. In recent years, there is no simple reproduction of labor potential. The number of people retiring is higher than the number of those entering working age. Existing trends in the reproduction of labor potential, especially the process of depopulation, in the near future require increased investment in the economically active population and the introduction of labor-saving technologies is the main direction to prevent labor shortages. Considering the labor potential as a natural basis of human capital, the authors conclude that in a demographic crisis, investment in human resources is the key to economic growth and overcoming labor shortages, strengthening the human resources of society.To draw the attention of scientists and specialists to the need to deepen research into the features of the formation of human capital in the regions, taking into account the demographic situation and trends in the development of their labor potential.The article considers methodological approaches to the economic evaluation of human capital, methodological approaches for calculating the human capital index are proposed. Areas of targeted investment in labor potential to ensure its expanded reproduction are proposed.